A portable roller ski rolling resistance measurement system - Ainegren, M.; Carlsson, P.; Tinnsten, M. (Procedia Engineering, 2013)
Roller skis are used by cross-country skiers, biathletes and ski-orienteers for their snow-free training and in roller ski competitions. Additionally, much of the current sports research into the physiology and biomechanics of cross- country skiing is conducted indoors on treadmills using roller skis. For elite athletes, the differences in performance are quite small, thus emphasising the importance of knowing the roller skis` rolling resistance coefficient, especially in connection to research and roller ski competitions. The purpose of this study was to develop a roller ski rolling resistance measurement system (P-RRMS) that is portable and therefore useful in different contexts and locations. The P-RRMS was designed as a small treadmill, equipped with roller ski stabilizing lateral supports and a screwed bar for applying different vertical loads on the roller ski. The design uses only one force sensor, with possible measurements of three directions of force and torque around three axes. The weight of the P-RRMS is 100 kg and it is equipped with wheels to facilitate transportation.